Collagen-Based Nanoparticles as Drug Delivery System in Wound Healing Applications - Kusnadi K; Herdiana Y; Rochima E; Putra ON; Mohd Gazzali A; Muchtaridi M (International Journal of Nanomedicine)
Kusnadi Kusnadi,1,2 Yedi Herdiana,1 Emma Rochima,3 Okta Nama Putra,1,4 Amirah Mohd Gazzali,5 Muchtaridi Muchtaridi1,6 1Department of Pharmacy Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Department of Pharmacy, Politeknik Harapan Bersama, Tegal, Central Java, 52147, Indonesia; 3Department of Fishery, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 4Research Center for Agroindustry, National Research and Innovation Agency (BRIN), Cibinong, Jawa Barat, 16911, Indonesia; 5School of Pharmaceutical Sciences, Universiti Sains Malaysia, Gelugor, Penang, 11800, Malaysia; 6Research Collaboration Centre for Radiopharmaceuticals Theranostic, National Research and Innovation Agency (BRIN), Sumedang, West Java, 45363, IndonesiaCorrespondence: Muchtaridi Muchtaridi, Email muchtaridi@unpad.ac.idBackground: Conventional wound dressings often adhere to wounds and can cause secondary injury due to their lack of anti-inflammatory and antibacterial properties. In contrast, collagen-based nanoparticles (NPs) as drug delivery systems exhibit both biocompatibility and biodegradability, presenting a promising avenue for accelerating wound healing processes.Aims of Study: This review aims to provide a comprehensive overview of the mechanisms involved in wound healing, description of the attributes of ideal wound dressings, understanding of wound healing efficacy of collagen, exploring NPs-mediated drug delivery mechanisms in wound therapy, detailing the synthesis and fabrication techniques of collagen-based NPs, and delineating the applications of various collagen-based NPs infused wound dressings on wound healing.Methodology: This review synthesizes relevant literature from reputable databases such as Scopus, Science Direct, Google Scholar, and PubMed.Results: A diverse array of collagen-based NPs, including nanopolymers, metal NPs, nanoemulsions, nanoliposomes, and nanofibers, demonstrate pronounced efficacy in promoting wound closure and tissue regeneration. The incorporation of collagen-based NPs has not only become an agent for the delivery of therapeutics but also actively contributes to the wound healing cascade.Conclusion: In conclusion, In brief, the use of collagen-based NPs presents a compelling strategy for expediting wound healing processes.Keywords: wound healing, biodegradability, nanoparticles, fabrication techniques, collagen